(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the influence that soil physical attributes can exert on edaphic entomofauna, considering an area of Fallow and another of Native Forest, collecting soil samples at depths 0 - 20 cm and 20 - 40 cm, totaling 49 samples per depth, totaling 98 samples per area, evaluating: soil density (SD), macroporosity (MAC), microporosity (MIC), total porosity (PT), gravimetric (UG) and volumetric (UV) humidity and soil penetration resistance (RPS), with collection of entomofauna at each sampling point. A total of 3,098 insects were collected, with the Formicidae family having the largest number of individuals and the order Coleoptera the largest number of families. The Principal Component Analysis found a relationship between the families Staphylinidae, Cleridae, Scarabaeidae, Bostrichidae, Culicidae, Blattidae, Scolytidae and Termitidae to the PT and UG in the Native Forest area. In the Fallow area, Staphylinidae, Curculionidae, Tenebrionidae, Scarabaeidae and Blattidae showed greater proximity to UV, UG, MAC and PT. In the geoestatistical analysis the matern, spherical, Gaussian, exponential and cubic semivariogram models were fitted to the soil attributes. In the edaphic fauna, the circular, exponential, cubic, spherical and Gaussian covariogram models were fitted. The results indicate the importance of soil physical characteristics, which interfere in the establishment of edaphic entomofauna.